HETEROSIS STUDIES FOR YIELD AND YIELD COMPONENTS IN GREENGRAM [Vigna radiata (L.) Wilczek] - ANAMIKA NATH; S. R. MALOO (The Bioscan, 2024)
Twenty eight hybrids of greengram along with their eight parental lines in 8 x8 half diallel fashion excluding reciprocal crosses were studied to assess the extent of heterotic effects over mid and better parent for yield and nine component characters. Out of 28 F1 hybrids, two crosses BM-4 x PDM-139 and RMG-1035 x RMG-1045 showed superior per se performance with significant positive heterosis for seed yield and most of the yield contributing characters. IPM 99-125 X ML 131 exhibited high heterosis for100 seed weight and harvest index, where as cross RMG 344 X RMG -1045 showed excellent heterosis for plant height and pods per cluster. Based on heterotic studies, the best direct yield contributing character were pods per cluster, pods per plant, plant height, 100 seed weight and harvest index. These hybrids could be utilized for developing high yielding mungbean cultivars.